Linking Glacial‐Interglacial States to Multiple Equilibria of Climate. Issue 17 (10th September 2018) - Ferreira, David; Marshall, John; Ito, Takamitsu; McGee, David
Abstract: Glacial‐interglacial cycles are often described as an amplified global response of the climate to perturbations in solar radiation caused by oscillations of Earth's orbit. However, it remains unclear whether internal feedbacks are large enough to account for the radically different glacial and interglacial states. Here we provide support for an alternative view: Glacial‐interglacial states are multiple equilibria of the climate system that exist for the same external forcing. We show that such multiple equilibria resembling glacial and interglacial states can be found in a complex coupled general circulation model of the ocean‐atmosphere‐sea ice system. The multiple states are sustained by ice‐albedo feedback modified by ocean heat transport and are not caused by the bistability of the ocean's overturning circulation. In addition, expansion/contraction of the Southern Hemisphere ice pack over regions of upwelling, regulating outgassing of CO2 to the atmosphere, is the primary mechanism behind a large pCO2 change between states. Plain Language Summary: For the last three million years, Earth's climate has oscillated between interglacial states (like today's climate) and glacial states (when ice sheets covered North America and Scandinavia). The dynamics of these glacial‐interglacial cycles (GICs) remains elusive. Here we provide evidence that GICs may be supported by multiple equilibrium of Earth's climate. In a coupled climate model with idealized geometry, we reveal two equilibrium states that coexist for the same external forcing. These states, which are sustained by ice‐albedo feedback modified by ocean heat transport, resemble the glacial and interglacial states. If confirmed, a link between GICs and multiple stable states would have a profound impact on our interpretation of the paleo‐record, and notably on the relationship between changes in the insolation due to Earth's orbital cycles and GICs. This link may provide an answer to puzzling aspects of the GIC, for example, why their amplitude is so regular despite the highly variable magnitude of insolation change during glacial terminations. In our perspective, the GIC's amplitude is primarily set by the separation between the multiple states (an intrinsic property of the unperturbed system) rather than by the forcing. The latter then provides the kick to trigger the transition from one state to the other. Key Points: Multiple equilibria of the global climate are found in a coupled ocean‐atmosphere‐sea ice general circulation model The two equilibrium states exhibit similarities with the present day climate and that of the Last Glacial Maximum The amplitude of the glacial‐interglacial cycles may be set by such equilibrium states, rather than by the forcing and feedbacks